Pelatihan Praktikum IPA Inovatif Berbasis Chemlab bagi Siswa dan Guru IPA SMP - Uliyandari, Mellyta Mellyta; Sutarno, Sutarno Sutarno; Gultom, Fades Br (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2025)
SMP Plus Ja-Alhaq Bengkulu is one of the private junior high schools in Bengkulu City that does not yet have adequate laboratory facilities. One solution to this problem is conducting virtual practicum using the chemlab application. The advantage of learning with chemlab is its practicality and ease of use, as well as the fact that it does not require many expensive tools and materials as in a real laboratory. This community service aimed to provide innovative science practicum training based on chemlab for students and science teachers at SMP Plus Ja-Alhaq. The program was carried out using the Technical Assistance Model in the form of training and mentoring activities. The training focused on explaining how to use the chemlab application, its features, and its functions, while the mentoring involved hands-on practice of applying chemlab in science practicum. The results of this activity showed that both students and teachers were able to use chemlab as a practicum medium to conduct science experiments virtually, thereby enhancing students’ motivation and learning outcomes.